Two New Flavonoids from the Leaves of Baccharis oblongifolia (Ruiz and Pav.) Pers. (Asteraceae) - Paulo R. F. Zampieri; Cinthia I. Tamayose; Oriana A. Fávero; Paulete Romoff; Marcelo J. P. Ferreira (Molecules, 2019)
In this work, two new flavonoids, oblongifolioside A (1) and oblongifolioside B (2), along with eight known compounds (3−10), are isolated from the leaves of Baccharis oblongifolia (Asteraceae). The new structures are established through spectroscopic data and the known compounds are identified by comparison with data reported in the literature. The compounds (1−10) are evaluated in relation to their antiradical properties. Compounds 1 and 2 are found to exhibit high antiradical activity compared to their respective non-acylated flavonoids.